2002
DOI: 10.1074/jbc.m109448200
|View full text |Cite
|
Sign up to set email alerts
|

Gemin5, a Novel WD Repeat Protein Component of the SMN Complex That Binds Sm Proteins

Abstract: The survival of motor neurons (SMN) protein is the product of the disease gene of spinal muscular atrophy and is found both in the cytoplasm and the nucleus, where it is concentrated in gems. SMN is part of a multiprotein complex that includes Gemin2, Gemin3, and Gemin4. The SMN complex plays an important role in the cytoplasmic assembly of small nuclear ribonucleoproteins (snRNPs) and likely other RNPs in pre-mRNA splicing and in the assembly of transcriptosomes. Here, we report the identification of an addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
123
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(125 citation statements)
references
References 48 publications
1
123
0
Order By: Relevance
“…SMN localizes diffusely throughout the cytoplasm, with intense nuclear signals corresponding to Cajal bodies (Liu and Dreyfuss, 1996;Matera and Frey, 1998). Based on the known protein-protein interactions, organization of the complex centers around SMN, which directly interacts with itself, Gemin2, Gemin3, Gemin5, and Gemin8 Lorson et al, 1998;Charroux et al, 1999;Meister et al, 2000;Baccon et al, 2002;Gubitz et al, 2002;Pellizzoni et al, 2002a;Carissimi et al, 2006a;Battle et al, 2007;Otter et al, 2007). Gemin8 is thought to recruit Gemin6, Gemin7, and unr-interacting protein (UNRIP/STRAP), whereas Gemin3 brings Gemin4 into the complex Baccon et al, 2002;Carissimi et al, 2005Carissimi et al, , 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…SMN localizes diffusely throughout the cytoplasm, with intense nuclear signals corresponding to Cajal bodies (Liu and Dreyfuss, 1996;Matera and Frey, 1998). Based on the known protein-protein interactions, organization of the complex centers around SMN, which directly interacts with itself, Gemin2, Gemin3, Gemin5, and Gemin8 Lorson et al, 1998;Charroux et al, 1999;Meister et al, 2000;Baccon et al, 2002;Gubitz et al, 2002;Pellizzoni et al, 2002a;Carissimi et al, 2006a;Battle et al, 2007;Otter et al, 2007). Gemin8 is thought to recruit Gemin6, Gemin7, and unr-interacting protein (UNRIP/STRAP), whereas Gemin3 brings Gemin4 into the complex Baccon et al, 2002;Carissimi et al, 2005Carissimi et al, , 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…The core SMN complex consists of SMN and Gemins2-8, and localizes to both the cytoplasm and nucleoplasm (Fischer et al 1997;Charroux et al 1999Charroux et al , 2000Gubitz et al 2002;Pellizzoni et al 2002;Carissimi et al 2006). Recent work by Otter et al (2007) revealed that SMN, Gemin7, and Gemin8 form a central complex to which the other Gemins peripherally associate via multiple interactions.…”
mentioning
confidence: 99%
“…The major U snRNAs (U1, U2, U4, and U5) are transcribed in the nucleus and transported to the cytoplasm, where direct interaction with the SMN complex has been demonstrated (Yong et al 2004;Golembe et al 2005). All of the SMN core complex components, with the exception of Gemin2, have been shown to associate with various subsets of so-called Sm proteins (SmB/BЈ, SmD1-3, SmE, SmF, and SmG) that can form a heptameric ring-like structure, known as the Sm core, in the presence of target U snRNAs (Fischer et al 1997;Charroux et al 1999Charroux et al , 2000Baccon et al 2002;Gubitz et al 2002;Pellizzoni et al 2002;Carissimi et al 2006). Sm core formation depends on the presence of a 6-to 8-nucleotide (nt) "Sm site" on the U snRNAs .…”
mentioning
confidence: 99%
“…The SMN complex is comprised of several proteins (many still unidentified), including Gemin2-8 and UNRIP (UNR-interacting protein, or STRAP) [Charroux et al, 1999;Charroux et al, 2000;Baccon et al, 2002;Gubitz et al, 2002;Pellizzoni et al, 2002;Carissimi et al, 2006]. The best characterized function of the complex is in the assembly of small nuclear ribonucleoproteins (snRNPs), which are involved in several aspects of RNA metabolism [see Workman et al, 2012 for a review].…”
Section: Smn: How Many Functions Can a Single Protein Possess?mentioning
confidence: 99%
“…However, because SMN is part of a very large multimeric complex, it is possible that SMND7 is stabilized in vivo due to its association with other proteins in the complex [Burghes and Beattie, 2009]. In favor of this hypothesis is the observation that expression of the SMND7 isoform in a Smn À/À ; SMN2 þ/þ background dramatically improves the survival of a severe mouse model of the disease [Le et al, 2005].The SMN complex is comprised of several proteins (many still unidentified), including Gemin2-8 and UNRIP (UNR-interacting protein, or STRAP) [Charroux et al, 1999;Charroux et al, 2000;Baccon et al, 2002;Gubitz et al, 2002;Pellizzoni et al, 2002;Carissimi et al, 2006]. The best characterized function of the complex is in the assembly of small nuclear ribonucleoproteins (snRNPs), which are involved in several aspects of RNA metabolism [see Workman et al, 2012 for a review].…”
mentioning
confidence: 99%